CCAFS knowledge and evidence inform World Bank investments in agricultural development - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
In 2018 alone, technical advice and knowledge products from CGIAR centers and CCAFS shared with project design teams contributed to improvements in at least 52 large agricultural projects and programs in low- and middle-income countries supported by World Bank grants and loans.